The Effect Of Concentration And Type Of Soaking Media (Water, Alcohol, Salt, And Vinegar) On Decreasing Oxalate Levels (Washability) In Porang - Sugiarto, Bambang; Setyawan, Adhi; Nurmalitasari, Octavia; Sulistyowati, RR Endang (Program studi Teknik Kimia UNS, 2023)
ABSTRACT. Porang tubers (Amorphophallus oncophyllus) contain very high rates of glucomannan and have many benefits in various fields of health, pharmaceutical, industrial, and food fields. Besides having great benefits, porang tubers contain calcium oxalate which causes itching if consumed directly, irritation and kidney stones. The purpose of this study was to make porang tubers free from oxalate content by using various concentrations and types of immersion media on porang. The types of immersion media are water, salt, alcohol, and vinegar. Oxalate rates were analyzed by permanganometric titration method. The results of the diced porang immersion in this study showed that water with a temperature of 70°C with an immersion time of 120 minutes, salt solution at a concentration of 14% with an immersion time of 90 minutes, alcohol with a concentration of 40% with a soaking time of 30 minutes, and vinegar with a concentration of 30% with an immersion time of 150 minutes is the optimal result. While the porang immersion with long slices obtained optimal results in water with a temperature of 50°C with an immersion time of 150 minutes, salt solution at a concentration of 14% with an immersion time of 150 minutes, alcohol with a concentration of 60% with an immersion time of 150 minutes, and vinegar acid with a concentration of 20% with an immersion time of 150 minutes. In the optimal results of the dice, the oxalate content in water immersion decreased by 2.4%, salt solution decreased by 68.4%, alcohol decreased by 24.6%, and vinegar decreased by 11.8%. In the optimal results of the spring roll filling, the oxalate content in water immersion decreased by 2.4 %, salt solution decreased by 7.3%, alcohol decreased by 19.7%, and vinegar decreased by 11.8%.Keywords: Porang, Calcium oxalate,Permanganometric